Can Tax Incentives for Electronic Payments Reduce the Shadow Economy? : Korea's Attempt to Reduce Underreporting in Retail Businesses - Sung, Myung Jae; Awasthi, Rajul; Lee, Hyung Chul (World Bank, Washington, DC, 2017)
Increasing tax revenues by reducing the shadow economy has been a central goal of tax policy and administration in the Republic of Korea since the National Tax Service was established as an independent agency in 1966. This paper examines the Tax Incentive for Electronically Traceable Payments, which was introduced by the Korean tax authorities in 1999 to promote payments made using credit cards, debit cards, and electronic cash receipts in business-to-consumer transactions. The tax incentive allows wage and salary earners to claim tax deductions for eligible purchases made using electronically traceable payments when they file their year-end income tax settlements. The tax incentive scheme greatly contributed to changing the Korean economy into a cashless economy over the past decade and a half. Card payments as a ratio of Korea's gross domestic product have ranked the highest in the world since 2005, reaching 49 percent in 2014. The Tax Incentive for Electronically Traceable Payments scheme has changed the taxpayer ratio over business income earners from stagnant at around 30 percent through the late 1990s, to approximately 80 percent at present. The effective personal income tax rate for business income followed a continuous upward trend, from 3.4 percent in 1998 to 6.3 percent in 2013. The total revenue increase driven by the tax incentive scheme was estimated as W 3.4 trillion, with the scheme's costs reaching W 1.9 trillion. The net gain was an estimated W 1.4 trillion (approximately US$1.3 billion), which increased personal income tax revenue by 4.2 percent. The tax incentive scheme also had a positive impact on income redistribution, decreasing the Gini coefficient by 0.11 percentage points.